Development and validation of recycled carbon fiber-based binder tapes for automated tape laying processes. (September 2019) - Rimmel, Oliver; May, David; Goergen, Christian; Poeppel, Artur; Mitschang, Peter
The current growth in use of fiber reinforced polymer composites causes a strongly increasing amount of waste. Current approaches for fiber reinforced polymer composites recycling usually not exploit the potential of endless fibers as they are shortened during recycling and will not be properly aligned in the final product. Considering this, the present work aimed at the development of a recycling process for long recycled carbon fibers, where fiber length is preserved and load-related fiber orientation is possible. The starting point for the presented work was so-called slivers, which are long bundles of fibers resulting from a carding process that has been applied to fiber scrap. The main focus of this work was on the development of a binder mesh application rig that processes the sliver to a binder tape, processable in an automated tape laying process, which in turn required modifications to adapt to the novel tape. The functionality of the binder tape manufacturing process was validated with long recycled carbon fibers slivers with linear density of 4 g/m and fiber lengths between 70 and 120 mm. With the binder tape preform manufactured this way, two alternative routes for composite manufacturing were tested. First, the amount of binder was set so high that direct thermoplastic pressing of the preforms was possible. Second, the amount of binder was minimized, and the preforms were infiltrated with a thermoset resin system via resin transfer molding. While the thermoplastic route showed very deficient fiber–matrix adhesion, with the thermoset route, ≈68% of stiffness and ≈31% of strength of virgin fiber-based composites could be achieved in fiber direction in a unidirectional lay-up.